Growth in Environmental Footprints and Environmental Impacts Embodied in Trade: Resource Efficiency Indicators from EXIOBASE3. (24th February 2018) - Wood, Richard; Stadler, Konstantin; Simas, Moana; Bulavskaya, Tatyana; Giljum, Stefan; Lutter, Stephan; Tukker, Arnold
Summary: Most countries show a relative decoupling of economic growth from domestic resource use, implying increased resource efficiency. However, international trade facilitates the exchange of products between regions with disparate resource productivity. Hence, for an understanding of resource efficiency from a consumption perspective that takes into account the impacts in the upstream supply chains, there is a need to assess the environmental pressures embodied in trade. We use EXIOBASE3, a new multiregional input‐output database, to examine the rate of increase in resource efficiency, and investigate the ways in which international trade contributes to the displacement of pressures on the environment from the consumption of a population. We look at the environmental pressures of energy use, greenhouse gas (GHG) emissions, material use, water use, and land use. Material use stands out as the only indicator growing in both absolute and relative terms to population and gross domestic product (GDP), while land use is the only indicator showing absolute decoupling from both references. Energy, GHG, and water use show relative decoupling. As a percentage of total global environmental pressure, we calculate the net impact displaced through trade rising from 23% to 32% for material use (1995–2011), 23% to 26% for water use, 20% to 29% for energy use, 20% to 26% for land use, and 19% to 24% for GHG emissions. The results show a substantial disparity between trade‐related impacts for Organization for Economic Cooperation and Development (OECD) and non‐OECD countries. At the product group level, we observe the most rapid growth in environmental footprints in clothing and footwear. The analysis points to implications for future policies aiming to achieve environmental targets, while fully considering potential displacement effects through international trade.